A Cross-Sectional Study on Mental Health Problems of Medical and Nonmedical Students in Shandong During the COVID-19 Epidemic Recovery Period - Xiaolei Zheng; Yuji Guo; Hui Yang; Liyan Luo; Bailiu Ya; Hong Xu; Zhiwei Xue; Qing Li; Jiale Shi; Jianzhong Bi; Wen Ma; Ping Wang (Frontiers in Psychiatry, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has resulted in a plethora of psychological problems worldwide since its onset in December 2019. In the upheaval period, compared with medical college students, nonmedical students' psychological state deserves additional concern due to their lack of medical knowledge. Although the epidemic in China has been largely controlled for several months, the mental health problems resulting from the COVID-19 epidemic persist to this day. In this study, we assessed the mental health problems and associated risk factors experienced by nonmedical vs. medical college students in universities of Shandong Province during the COVID-19 epidemic recovery period.Methods: An online survey was conducted over the period from 17 to 19 December 2020. A total of 954 Chinese college students (486 nonmedical and 468 medical students) from three universities of Shandong Province participated in the survey. Mental health variables were assessed with use of Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Insomnia Severity Index (ISI).Results: Compared with medical students, nonmedical college students had higher prevalence rates of depression (53.9 vs. 46.4%; p = 0.020) and insomnia (28.0 vs. 22.4%, p = 0.049), as well as higher total scores on the PHQ-9 (p = 0.03) and ISI (p < 0.01). Among nonmedical college students, being female and native of non-Shandong were risk factors for anxiety and depression (p < 0.01), while only native of non-Shandong for insomnia (p < 0.01). Among medical students, age (p < 0.01) and living in rural areas (p = 0.04) were risk factors for depression, while only age (p < 0.05) was a risk factor for anxiety and insomnia.Conclusion: Nonmedical college students in the universities of Shandong Province had more mental health problems and more risk factors for developing them during the COVID-19 epidemic recovery period than medical students. These nonmedical students require additional attention and recovery programs to alleviate the increased incidence of psychological problems related to COVID-19.